The factors Related to Maternal-Fetal Attachment: Examining the Effect of Mindfulness, Stress and Symptoms during Pregnancy - Sophie Huey-Ming Guo (Archives of Nursing Practice and Care - Peertechz Publications, 2019)
Background: The development of a successful relationship between a mother and her developing fetus to foster maternal behavior attainment. Diverse factors such as psychophysiological elements influence the maternal-fetal relationship. Mindfulness, a psychological process, increasingly apples to the research of pregnant women's wellbeing. However, most studies focus solely on physiological outcomes; few consider the maternal-fetal bonding.  Purpose: This research aims to investigate whether factors of stress, symptoms during pregnancy and mindfulness systematically related to maternal-fetal attachment.  Methods: Data were collected from 339 pregnant women, which were recruited from two hospitals in Taiwan, using the following questionnaires: the mindfulness scale, the symptom scale, the pregnancy stress scale during pregnancy, and the maternal fetal attachment scale. A path analysis approach was used to test the relationship.  Results: Pregnancy stress is the most robust factor of maternal-fetal attachment. The mindfulness and stress during pregnancy both have significant direct effects on maternal-fetal attachment, ß = .46, and ß = 22, all p < 0.00, respectively. The mindfulness has a significant inverse, direct effect (ß = -.13, p < 0.05) on stress during pregnancy. But the variable of symptoms during pregnancy is no significant effect on maternal-fetal attachment. The model proposed in this study accounts for 22.5% (R2) variance in the relational model of maternal-fetal attachment. Conclusions: Given that the maternal mindfulness direct and indirect effect through stress variable on mother developing a closer connection with her babies, screenings of the relational elements should be incorporated into prenatal education programs.